The Value of Enabling Teachers to Research Their Practice - Lindsey N. Conner; Janinka Greenwood (New Zealand Journal of Teachers' Work)
This paper reports a project in which teachers used small action-research projects to investigate how they were responding to the diversity of their students in terms of planning and teaching. The project, funded by the New Zealand Ministry of Education through the Teaching and Learning Research Initiative fund (TLRI), involved teachers investigating self-chosen issues related to the diversity within their own sphere of practice. They were mentored through the research process by experienced tertiary researchers and by their peers in a series of regular meetings and conversations. As a result of participating in this project, the teachers developed an awareness of themselves as practitioner-researchers and acquired a foundational, though still emergent, understanding of research paradigms and research processes. In this paper, we reflect on the process, the nature of the outcomes, the value of such collaborative research partnerships, and the experiential learning of the teachers.